2018
DOI: 10.3390/en11030608
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Coil System for Generating Uniform Magnetic Fields inside a Cubic Magnetic Shield

Abstract: Ultra-low magnetic fields have drawn lots of attention due to their important role in scientific and technological research. The combination of a magnetic shield and an active compensation coil is adopted in most high performance magnetically shielded rooms. Special consideration needs to be taken in the coil design since the magnetic shield significantly affects the uniformity of the magnetic field that is generated by the coil. An analytical model for the magnetic field calculation of the coil inside a cubic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 21 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…To ensure that the boundary conditions are properly fulfilled, reflections have to be calculated recursively so that the mirrored currents are themselves mirrored. Here, the effect that the mu-metal walls have on the form of the field produced by the balanced coils operating inside the MSR has been modelled via the addition of a truncated set of mirror currents 17,18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that the boundary conditions are properly fulfilled, reflections have to be calculated recursively so that the mirrored currents are themselves mirrored. Here, the effect that the mu-metal walls have on the form of the field produced by the balanced coils operating inside the MSR has been modelled via the addition of a truncated set of mirror currents 17,18 .…”
Section: Methodsmentioning
confidence: 99%
“…This was not considered in the process of coil design here, though similar interactions have been incorporated into gradient coil design methods for MRI 16 . It has been shown that this interaction can be modelled by a method of images approach 17,18 . This was utilised to simulate the effects of interactions on the efficiency and homogeneity of the designed coils when operated inside a MSR.…”
Section: Introductionmentioning
confidence: 99%
“…There are some reasons for the errors between the simulation and the experiment results. (1) The actual MSR is made of pieces of a permalloy plate, and the air gap between these plates can cause magnetic flux leakage, which reduces the shielding factor of the MSR [14]. In addition, the actual MSR has a door in each layer, and several holes are distributed in each surface, edge, and corner, which will influence the shielding factor.…”
Section: The Shielding Factors When the External Fields Are Sine Wavesmentioning
confidence: 99%
“…Planar high-permeability materials have been incorporated into optimization procedures using the method of mirror images [26,27] to determine the total magnetic field generated by a static current source inside a magnetically shielded room [28][29][30][31]. Similar work in magnetic resonance imaging has investigated the interaction of switched magnetic field gradients with high-conductivity materials used for passive shielding [32].…”
Section: Introductionmentioning
confidence: 99%